An Assessment of the Implementation of Forest Curriculum in a Private School in Abu Dhabi, UAE. - ALMENHALI, AFAF AHMED (2024)
This study determines the effectiveness of the implementation of the forest curriculum in a private pre-school in Abu Dhabi, UAE. This dissertation aims to evaluate the positive impact of nature-based learning in private pre-schools, to determine the challenges of implementation, and to propose effective implementation strategies with regard to the forest curriculum. Employing a mixed-methods approach, quantitative data were collected through a questionnaire distributed to a cohort of 42 teachers. Additionally, qualitative data were gathered through an interview with the principal of the school to provide insights into the lived experiences of the participants. This study contributes valuable insights to the field of curriculum evaluation, offering a holistic understanding of the impact of the forest curriculum on students. In addition, with the UAE moving towards sustainability, there has come a need to support nature curricula, which are represented by forest schools. Forest schools can have a positive impact on the environment and on sustainability by fostering a deep connection with nature, promoting environmental awareness, instilling sustainable practices, and contributing to the overall well-being of individuals and communities. The research findings underscore the importance of curriculum alignment with 21st-century skills and the need for ongoing professional development to support educators in navigating integrated forest school approaches. Further research involving a larger and more diverse sample is recommended to confirm and extend these initial results. The implications with regard to integrating the forest curriculum in government schools should be discussed.